Immunoregulation of Macrophages by Controlling Winding and Unwinding of Nanohelical Ligands (Adv. Funct. Mater. 37/2021). (9th September 2021) - Bae, Gunhyu; Jeon, Yoo Sang; Ko, Min Jun; Kim, Yuri; Han, Seong‐Beom; Thangam, Ramar; Kim, Wonsik; Jung, Hee Joon; Lee, Sungkyu; Choi, Hyojun; Min, Sunhong; Hong, Hyunsik; et al.
Abstract : Macrophage Polarization In article number 2103409, Young Keun Kim, Heemin Kang, and co‐workers present an adhesive nanohelical nanostructure that is partially affixed to the surface, which can be actively manipulated to wind in any direction. This active winding modulates integrin recruitment onto the adhesive nanostructure at a single cell level to mediate an assembly of adhesion structures that stimulates regenerative immunomodulation.